Estructurando nodos de actividades (2017)
This project based in the metro proposal of todays' mayor Enrique Peñalosa looks forward for a design which reflects the new possibilities that will come with the elevated metro. For this reason, the location was chosen because of the possibilities of density, integration of the natural environment and my personal life experience. After the topological analysis, the zone shows the dominance of residences around the area with commerce along the principal streets such like AV Primera de Mayo and Carrera 50. Also, the percentage of green zones is very high, almost meeting the Bogotas's average of 4,3 m2/hab with a 4,25m2/hab. Likewise, the physical conditions create problems of insecurity, bad pedestrian circulation and building in poor conditions. The strategies to approach these problems are rehabilitation, renaturation and reconnection. The first strategy, the rehabilitation is based on the provision of three types of nodes, the great articulators of the neighborhood with the city that correspond to the needs of the neighborhood on a metropolitan scale, social activities that correspond to a local scale, and the reconfigurators of the existing housing that provoke the improvement of the security and quality inside the blocks. The second strategy, renaturation is the relaxation and interaction at the level with rio seco. The third, the reconnection is to introduce circuits of pedestrian and bicycle mobility integrated with the pre-existing and future mobility systems. Finally, nodes are proposed along el rio seco, whose main point are the blocks surrounding the future metro station. The buildings of these blocks are a sport center of professional level and a building of housing and commerce, where the first one is developed in detail and the second is presented in a schematic design.--Tomado del Formato de Documento de Grado.